Improving the improvisational pelvic circumferential compression technique for open-book pelvic fractures using a simulation model and a sphygmomanometer. Issue Volume 166:Issue E(2020) (22nd May 2019) - Rega, Paul Patrick; Fink, B; Sexton, M; Schneiderman, J; Kakish, E; McKenzie, N; Kenney, K; Jones, C
Abstract : Background: Open-book pelvic fractures are associated with significant mortality. Emergency management may require a commercial pelvic circumferential compression device to reduce the fracture and compress haemorrhaging pelvic vasculature. Standard, commercial, twin-sized bedsheets are acceptable should commercial devices be unavailable. However, obese victims or personnel with insufficient body strength may impede successful reduction. Objective: To demonstrate the value of an improvisational windlass (intravenous pole) in improving the ability to reduce an open-book pelvic fracture. Methods: The Institutional Review Board-approved study involved 28 diverse healthcare students and emergency medicine residents. Each participant's demographic information and physical characteristics were recorded. A METIman was prepared with knee and ankle binding and a sphygmomanometer set at 40 mm Hg placed over the symphysis pubis. Two-person teams were randomly selected to place a bedsheet at greater trochanter level and atop the sphygmomanometer. The bedsheet was secured with maximum effort by the pairs and the pressure recorded. Following this, the pairs inserted an intravenous pole in the knot and torqued the pole to maximum effort and a repeat pressure recorded. Results: The mean increase in pressure using only the bedsheet was 106.43 mm Hg per team. With bedsheet and intravenous pole, the mean pressure increase was 351.79 mm Hg per team. The difference was statistically significant (independent samples t-test: t = 17.177, p < 0.001, 95% CI (216.65 to 274.07 mm Hg). There was no correlation between pressure increases and the individual physical characteristics of the subjects (r = − 0.183, p = 0.352). Conclusions: Regardless of personnel's physical attributes, the addition of an improvisational windlass to a pelvic circumferential compression bedsheet can improve the ability to reduce an open-book fracture, especially in obese victims.